Consider this solution to a problem.

Problem: -4(6 - y) + 4 = -4

Step 1: -24 - 4y + 4 = -4

Step 2: -20 - 4y = -4

Step 3: -4y = 16

Step 4: y = 4

Choose the number of the step where the first mistake was made.

Then, solve the equation correctly.

Problem: -4(6 - y) + 4 = -4

Step 1: -24 - 4y + 4 = -4

Step 2: -20 - 4y = -4

Step 3: -4y = 16

Step 4: y = 4

Choose the number of the step where the first mistake was made.

Then, solve the equation correctly.

The first mistake was made in

Step 1 should read: -24 + 4y + 4 = -4

-4(6 - y) + 4 = -4

-24 + 4y + 4 = -4 {used distributive property with -4}

4y - 20 = -4 {combined like terms}

4y = 16 {added 20 to each side}

**Step 1**, by not distributing the -4 correctly.Step 1 should read: -24 + 4y + 4 = -4

**Correct steps and solution:**-4(6 - y) + 4 = -4

-24 + 4y + 4 = -4 {used distributive property with -4}

4y - 20 = -4 {combined like terms}

4y = 16 {added 20 to each side}

**y = 4**{divided each side by 4}**- Algebra House**